2019
DOI: 10.1073/pnas.1813049116
|View full text |Cite
|
Sign up to set email alerts
|

Parental divorce is not uniformly disruptive to children’s educational attainment

Abstract: Children whose parents divorce tend to have worse educational outcomes than children whose parents stay married. However, not all children respond identically to their parents divorcing. We focus on how the impact of parental divorce on children’s education varies by how likely or unlikely divorce was for those parents. We find a significant negative effect of parental divorce on educational attainment, particularly college attendance and completion, among children whose parents were unlikely to divorce. Famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 35 publications
5
45
0
3
Order By: Relevance
“…28,29 The results of this thesis nonetheless lend support to a growing number of studies in favor of the floor effects hypothesis, whereby youth in educated or highly educated families are at higher risk of lower academic achievement following a parental divorce relative to peers with less educated parents. [28][29][30][31][32] Two related findings form the foundation of this conclusion. Firstly, a divorce was not statistically significantly related to the GPA among adolescents with two less educated parents (ISCED 0-2).…”
Section: Heterogeneity In the Associations Between Divorce And Adolesmentioning
confidence: 62%
See 1 more Smart Citation
“…28,29 The results of this thesis nonetheless lend support to a growing number of studies in favor of the floor effects hypothesis, whereby youth in educated or highly educated families are at higher risk of lower academic achievement following a parental divorce relative to peers with less educated parents. [28][29][30][31][32] Two related findings form the foundation of this conclusion. Firstly, a divorce was not statistically significantly related to the GPA among adolescents with two less educated parents (ISCED 0-2).…”
Section: Heterogeneity In the Associations Between Divorce And Adolesmentioning
confidence: 62%
“…It provides an elaborate social safety net through free access to the health care system and access to sickness, unemployment, and family-related benefits. Levels of absolute deprivation and income inequality in Norway is low [28,29], and the population is highly educated; 38.2% of all women and 30.1% of all men had completed some form of university-level education in 2019 [30]. Like in the other Nordic welfare states, the "dual-earner family" is strongly encouraged; public childcare and schools are highly subsidized, and generous parental leave rights (also for the father) have facilitated the combination of full-time employment and childcare among both mothers and fathers (see [31]).…”
Section: Introductionmentioning
confidence: 99%
“…For example, using matching methods and growth curve models, H. S. Kim () found that divorce negatively affects children's math test scores and interpersonal social skills. Brand, Moore, Song, and Xie () use propensity‐score analysis to show that divorce reduces educational attainment most for children whose parents were least likely to divorce. (But see Grätz [], which finds a different pattern in Germany using a sibling‐based fixed effects model.)…”
Section: Consequences Of Divorce and Repartneringmentioning
confidence: 99%
“…Treatment effect heterogeneity has important implications for social research and policy. The study of treatment effect heterogeneity can yield valuable insights into how scarce social resources are distributed in an unequal society (e.g., Brand 2010;Brand and Xie 2010;Heckman, Urzua, and Vytlacil 2006), how events differentially impact populations with different expectations of their occurrence (e.g., Brand and Simon Thomas 2014;Brand et al 2019;Clark 2010;Turner 1995), and what may explain response heterogeneity, including differential selection (e.g., Heckman and Vytlacil 2007;Zhou and Xie [forthcoming]; Zhou and Xie 2019). If policymakers understand patterns of treatment effect heterogeneity, they can more effectively assign different treatments to balance competing objectives, such as reducing costs and maximizing average outcomes (Davis and Heller 2017).…”
Section: Introductionmentioning
confidence: 99%
“…(adapted fromZhou and Xie [forthcoming] andBrand et al [2019]), we depict alternative ways in which we can interpret treatment effect heterogeneity. The darker shaded regions indicate a larger treatment effect magnitude (i.e., larger negative effects of college on proportion of time in low wage work).…”
mentioning
confidence: 99%